PEMBELAJARAN GERAK LURUS DENGAN MODEL COOPERATIVE LEARNING DISERTAI MEDIA VIDEOS TRACKER - Erin Wardani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Straight motion material is one of the science materials which is considered difficult for junior high school students. Many students do not understand the material well. In addition, teaching methods from teachers who are still very conventional also become one of the causes of students' lack of understanding. Lack of collaboration between students is also one of the causes of the low average students' understanding of straight motion material. Therefore, it is necessary to have an interesting learning process assisted with media that canimprove students' understanding in learning straight motion material. Byusing media videos trcaker with cooperative learning models selected toovercome these problems. The purpose of writing this work is to find outlearning that can improve students 'understanding of the material ofmovement and students' collaboration in learning. The method used in writing this work is using literature study, which is by collecting several relevant reference sources. The expected result of writing this work is to obtain learning and media that can improve students' understanding of motion material. Through cooperative learning with media videos trcaker, students will be able to analyze a problem regarding straight motion by discussing it with friends in groups so that it can increase the level of cognitive thinking and student collaboration. Keywords: learning media, learning model, science learning